Pengaruh Metode Hafalan Terhadap Hasil Belajar Peserta Didik di Kelas XI Ips 6 pada Mata Pelajaran Alqur’an Hadis di Man 1 Kabupaten Bogor - Nafilah Diana Kholidah; Suhendra; Bahrum Subagiya (Jurnal Dirosah Islamiyah, 2025)
The background of the problems in this study is that the learning method has not been maximized and the low interest in memorization methods, teaching methods that are not interesting, and classroom conditions that are not conducive. The formulation of this research problem is 1) how the influence of the memorization method on the subject of AlQur'an Hadith class XI IPS 6 in MAN 1 Bogor Regency, 2) how is the learning outcome in the subject of Al-Qur'an Hadith class XI IPS 6 in MAN 1 Bogor Regency, 3) whether there is an influence of the memorization method on the learning outcomes of students in class XI IPS 6 in the subject of Al-Qur'an Hadith in MAN 1 Bogor Regency. The purpose of this study is to find out whether there is an influence of the memorization method on the learning outcomes of students in class XI IPS 6 in the subject of Al-Qur'an Hadith in MAN 1 Bogor Regency. The framework of thinking in this study is variable X (method of memorizing the Qur'an, steps to use the memorization method, benefits of memorization, and advantages and disadvantages of the memorization method), variable Y (Judging from the results of the assessment of memorization scores for the odd semester of the 2023-2024 school year). This study uses a descriptive method with a quantitative approach. The results of the research conducted at MAN 1 Bogor Regency are known that there is a correlation of the influence of the memorization method on the learning outcomes of students. This is evidenced by a correlation test with a tcal value of 17.162 greater than the ttable at a significant level of 5%, namely 2.048 (17.162>2.048). The results of the calculation of the determination coefficient (R Square) of 0.913 which showed that the influence of the memorization method on the learning outcomes of students in class XI IPS 6 in the subject of Al-Qur'an Hadith was 91.3%, while the remaining 8.7% was influenced by other variables that were not included in this study. The significance value of 0.000 < 0.05 can be concluded that the influence of the memorization method on the learning outcomes of students in class XI IPS 6 in the subject of Al-Qur'an Hadith in MAN 1 Bogor Regency is acceptable.